Policy and institutional enablers of public–private partnerships in the electricity sector in Uganda: a multi-level and path dependence perspective. Issue 1 (11th December 2020) - Onyoin, Moses; Bovis, Christopher
Abstract : Purpose: This paper explains the evident disproportionality in the levels of adoption of the modality of public–private partnerships (PPPs) in Uganda by tracing the peculiar preconditions and enablers of the model's relative high adoption in the electricity sector. Design/methodology/approach: Key conceptual suggestions from historical institutionalism (HI), critical juncture and path dependence are used to orient the data collection and analysis. The direct experiences and perceptions of key informants involved in policy, regulation and operations in the electricity sector are thematically analyzed. Findings: The primacy of specific policy, institutional decisions and actions sequentially undertaken at the international, national and sectorial levels in shaping the conceivability and possibility of PPP modality is foregrounded. In particular, international advisory for the changed role of the state and the government's subsequent decision to enact and reenact specific institutional frameworks at the national and sectorial levels created important disruptions to the status quo and paved a new and relatively stable institutional path conducive for private sector participation. Research limitations/implications: Theoretically, the paper demonstrates the ability and power of HI to support the exploration and framing of multilevel and path-dependent explanations of institutional development and policy adoption. Practically, suggestions in terms of policy, legal and regulatory enablers for the adoption of PPP are made to shape practitioners' decision-making Practical implications: Practically, suggestions in terms of policy, legal and regulatory enablers for the adoption of PPP are made to shape practitioners' decision-making. Originality/value: The importance of considering factor combinations and sequences in explaining the emergence, adoption and proliferation of public policy instruments and phenomena is underscored. In addition, the discourse on PPPs is moved beyond rationalization on how to even out their adoption (and subsequently the associated benefits) across sectors.